2013
DOI: 10.1111/his.12133
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear GSK‐3β segregation in desmoid‐type fibromatosis

Abstract: Our data suggest that GSK-3β is an additional DF marker with an important role in the aetiopathogenesis of this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
6
2
Order By: Relevance
“…Meneghello et al. reported results inconsistent with those of our study, namely that mRNA expression of cyclin D was decreased in all desmoid cells harboring different mutation status compared with control cells, whereas that of Axin2 increased . This discrepancy between our studies might be due to differences in the control cells used.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Meneghello et al. reported results inconsistent with those of our study, namely that mRNA expression of cyclin D was decreased in all desmoid cells harboring different mutation status compared with control cells, whereas that of Axin2 increased . This discrepancy between our studies might be due to differences in the control cells used.…”
Section: Discussioncontrasting
confidence: 99%
“…Effectiveness of drugs had better be analyzed by not only cell viability test, but also gene expression patterns of target genes because downstream of Tcf/Lef transcription pathway should have crucial roles in tumorigenesis of desmoid tumors. Meneghello et al reported results inconsistent with those of our study, namely that mRNA expression of cyclin D was decreased in all desmoid cells harboring different mutation status compared with control cells, whereas that of Axin2 increased [28]. This discrepancy between our studies might be due to differences in the control cells used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These codons are the serine and threonine phosphorylation sites required for β-catenin degradation [ 116 , 117 ]. Therefore, these mutations make phosphorylation impossible and promote β-catenin nuclear translocation [ 118 ]. A high level of nuclear β-catenin staining is the conventional diagnostic marker for DFs.…”
Section: Desmoid-type Fibromatosis: a Pathology Arising From Wnt Pathmentioning
confidence: 99%
“…Although the morphologies of these tumors have been well characterized, their nature and pathogenesis have remained obscure for many years [6, 9]. According to the literature, the median age at the diagnosis of DFs is about 35 years, and the majority of patients are women [10].…”
Section: Discussionmentioning
confidence: 99%